Evolution of the magnetic hyperfine field profiles in an ion‐irradiated Fe60Al40 film measured by nuclear resonant reflectivity. (19th August 2021) - Andreeva, Marina; Smekhova, Alevtina; Baulin, Roman; Repchenko, Yurii; Bali, Rantej; Schmitz-Antoniak, Carolin; Wende, Heiko; Sergueev, Ilya; Schlage, Kai; Wille, Hans-Christian
Abstract : Nuclear resonant reflectivity (NRR) was measured from an Fe60 Al40 film irradiated by 20 keV Ne + ions with gradually varying fluences of 0–3.0 × 10 14  ions cm −2 . The evolution of the ferromagnetic onset, starting from the central part of the film and propagating towards the interfaces, was revealed by the fit of the NRR time spectra. Abstract : Nuclear resonant reflectivity (NRR) from an Fe60 Al40 film was measured using synchrotron radiation at several grazing angles near the critical angle of total external reflection. Using laterally resolved measurements after irradiation with 20 keV Ne + ions of gradually varying fluence of 0–3.0 × 10 14  ions cm −2, the progressive creation of the ferromagnetic A2 phase with increasing ion fluence was confirmed. The observed depth selectivity of the method has been explained by application of the standing wave approach. From the time spectra of the nuclear resonant scattering in several reflection directions the depth profiles for different hyperfine fields were extracted. The results show that the highest magnetic hyperfine fields (∼18–23 T) are initially created in the central part of the film and partially at the bottom interface with the SiO2 substrate. The evolution of the ferromagnetic onset, commencing at a fixed depth within the film and propagating towards the interfaces, has been directly observed. At higher fluence (3.0 × 10 14  ions cm −2 ) the depth distribution of the ferromagnetic fractions became more homogeneous across the film depth, in accordance with previous results.